Serological diagnosis of fasciolosis (Fasciola hepatica) in humans, cattle, and sheep: a meta-analysis - Drescher, Guilherme; Vasconcelos, Tassia Cristina Bello de; Belo, Vínicius Silva; Pinto, Mariane Marques da Guarda; Rosa, Jaqueline de Oliveira; Morello, Luis Gustavo; Figueiredo, Fabiano Borges (Frontiers in Veterinary Science, 2023)
Fasciola hepatica can cause problems in both animals and humans. Fasciolosis can be diagnosed through the indirect ELISA immunodiagnostic test. Serological diagnosis of Fasciola is based on recombinant antigens secreted by this worm. We used PubMed and Google Scholar databases to review the published literature on 'antigens with immunogenic potential' used in serological tests to identify antibodies against F. hepatica in humans, cattle, and sheep. Studies that investigated diagnostic tests with common reference standards were included in the sensitivity and/or specificity bivariate metaanalysis. In the quality and susceptibility to bias analysis of the 33 included studies, 26 fulfilled at least six (75%) of the eight QUADAS criteria and were considered good-quality papers. We found that most of the studies used native excretory-secretory antigens and recombinant cathepsin in ELISA tests for serological diagnosis of fascioliasis in humans, cattle, and sheep. The meta-analysis revealed that all antigens demonstrated good accuracy. The best results in terms of sensitivity (0.931 -2.5% confidence interval (CI) and 0.985 -97.5% CI) and specificity (0.959 -2.5% CI and 0.997 -97.5% CI) were found in human FhES. FhrCL-1, FhES, and FhrSAP-2 antigens gave the best results for the serum diagnosis of human and animal fasciolosis.